Study of Thermoelectric Properties of Indium Silicon Oxide Thin Films - Cerdeira, Joana Marques (2018)
Thermoelectric devices, which convert heat into electricity, are regarded as an environmentally friendly alternative to fossil fuels used as the main resource for energy production. In the last few decades, transparent oxide semiconductors and conductors, namely Indium oxide-based materials, have been studied and applied in thin film transistors and solar cells. Nevertheless, this group of materials has also been studied for thermoelectric applications. In this dissertation, amorphous Indium silicon oxide (ISO) thin films were sputtered at room temperature on glass substrate, under different oxygen contents in the argon and oxygen mixture. The thermoelectric properties were evaluated as a function of deposition conditions and post-deposition annealing parameters (temperature and time). These properties were analysed and correlated with respective structural, morphological, optical, and electrical properties. For films deposited with no oxygen and annealed at 300 ºC for 24 h, the Seebeck coefficient and electrical resistivity at room temperature were 68:6 VK1 and 4:7 102 cm, respectively. Thin films deposited at higher oxygen percentages showed, in turn, very low conductivity values not being possible to measure the Seebeck coefficient. The maximum power factor achieved was 10 Wm1K2 for the aforementioned annealing conditions. A simultaneous increase of the Seebeck coefficient and electrical conductivity was also observed, mainly due to scattering mechanisms which enhanced the Seebeck coefficient. Although ISO thin films properties present a good stability when submitted to different post-deposition conditions, further studies need to be performed in order to optimise the thermoelectric properties and hence the power factor.